Innovative paradigms in New Japanese art: a case study of Yokoyama Taikan's selected artworks - Mao Xing; Sarena Abdullah (Cogent Arts & Humanities)
Yokoyama Taikan is known as the 'giant of modern Japanese painting'. Throughout his life, he devoted himself to various fields, such as painting, art education, and art movement, making outstanding contributions to the reform of modern Japanese painting. The objective of this paper is to explore Yokoyama Taikan's reconstruction of 'Modern Japanese Painting' and reveal its underlying principles of artistic innovation. This aims to provide a better understanding of the modernisation and transformation of Japanese painting, especially through Taikan's artworks. This study offers an interpretive perspective different from traditional art history and aesthetics, focusing on three aspects within the theoretical framework of visual culture studies: the interpretation of visual symbols, the evolution of aesthetic perspectives, and the acceptance of popular art through the case study method. This theoretical framework enables the interpretation of the development of themes, colours, and forms in Yokoyama's works and the in-depth analysis of the strategies he employed to innovate 'New Japanese Painting'. This paper argues that Taikan's reconstruction and breakthrough of the traditional framework of Japanese painting liberates and transcends the boundaries of traditional artistic concepts and promotes its transition from tradition to modernity.